Penyelesaian Kredit Macet pada BPR Sinar Putra Mas Akibat Pandemi Covid-19 - Komang Vegayanthi; I Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna (Warmadewa Press, 2022)
Credit facilities are very useful for today's society, especially in terms of business and business. The condition of the COVID-19 pandemic has a significant impact in various aspects, one of which is the payment of credit. During the Covid-19 Pandemic, BPR Putra Mas felt the impact, namely in the form of bad credit incidents against several customers. This research is empirical research. Using the statutory approach (Statue Approach), the author of the Legal Concept Analysis Approach (Analytical and Conceptual Approach), and the Fact Approach (The Fact Approach). Primary data in empirical research is in the form of interviews with informants who are the Manager and Head of the Credit Section of BPR Sinar Putra Mas. The data techniques used were interview techniques and document study techniques. The results of this study are the factors that cause bad credit at BPR Sinar Putra Mas in broad outline into three. First, namely the debtor factor, Second, the creditor factor, and the three factors from Outside Debtors and Creditors (External). the steps of Rescheduling (Rescheduling), Reconditioning (Requirements), Restructuring (Rearranging), and Liquidation (Liquidation).